Comparative effect of tomato juice, walking, and their combination on blood pressure in prehypertension - Jane Christofanie; Budi Setiawan; Mira Dewi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
This study examined the individual and combined effects of tomato juice and increased daily walking on blood pressure in prehypertensive adults. A total of 34 sedentary participants aged 19–36 years were randomly assigned to four groups: control, tomato juice, walking, and a combination of both. The intervention lasted for 14 days, during which participants consumed 200 ml of unsalted tomato juice and/or increased their steps by a minimum of 5,000 steps per day (on average), tracked using health (iOS) or Google Fit (Android). Blood pressure was measured before and after the intervention and analyzed using paired t-tests (p<0,05). All intervention groups showed a reduction in systolic blood pressure, with the combination group showing the most significant decrease—from 128,75±4,20 to 110,50±6,05 mmHg (p=0,000) for systolic and from 82,50±8,40 to 74,74±3,92 mmHg (p=0,033) for diastolic pressure. A significant correlation between body mass index and blood pressure reduction was also observed, suggesting that body weight may influence the effectiveness of these lifestyle interventions.